Plotino: el sistema del Uno. Características generales - Uña Juárez, Agustín (Anales del Seminario de Historia de la Filosofía, 2002)
Plotinus’ thought is generally viewed as a “system”, the One’s system, wich embraces and considers the Totality as such, as a whole, ruled by the metaphysical law of the unity. Scholars as É. Bréhier, J. Moreau, G. Reale, J. Igal, A. H. Armstrong... agree to it. The present study tries to make explicit and interpret it, examining some basic features, or general traits, wich reveal the Plotinian doctrine from this same point of view. Therefore, the systematic side of Plotinus’ thought is here viewed as the really suitable mode, way or “mothodology” to think the Totality as a supreme unity, and to express the One’s ontology as a perfect whole. According to this interpretation, the system reflects the “synoptical” view of its same content, and shows it as the One’s “presence” in the whole reality and in the Plotinus’ intuitive mind, developed through an ordered series of concepts, in view of the mystical experience, to the union with the One, as the final goal.